CoTaS@Home: Uma solução de provisionamento de contexto das coisas para casas inteligentes como um serviço - Bradachi, João G. A.; Silva, Thais R. M. B.; Santana, Henrique de S.; Aylon, Linnyer B. R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16117, 2025)
Internet of Things applications in smart environments rely on data from smart objects, particularly on the context of things. To provide the academic community with a service for context provisioning, this paper introduces CoTaS@Home. An architectural model for a Context-as-a-Service system is presented, along with its partial implementation through modeling and simulation. Furthermore, a smart home environment was established with five scenarios for metrics analysis. Preliminary results indicate that the absence of context management negatively impacts the complexity for applications to discover smart objects with the required profiles as well as the network’s scalability.